PERANCANGAN SISTEM INFORMASI TRACKING PENJUALAN PRODUK ATK BERBASIS WEB - Lela Nurlaela; Tuhfatul Habibah Hasibuan; Nanda Andriani (Jurnal Komputer dan Teknologi, 2026)
The rapid development of information technology has encouraged businesses to utilize information systems to improve the effectiveness and efficiency of data management. Toko Meta, a stationery (ATK) store, still encounters challenges in managing product data, sales transactions, sales tracking, and report generation. These conditions result in inefficient data retrieval and limit the effectiveness of sales monitoring. This study aims to design a web-based Sales Tracking Information System for Toko Meta. The research employed a qualitative method with data collected through observation, interviews, and literature review. System requirements were analyzed using the PIECES method, while the system was developed using the System Development Life Cycle (SDLC). The application was developed using the Laravel framework, PHP programming language, and MySQL database. The results of this study are a web-based information system that provides features for user authentication, product management, sales transactions, sales tracking, and sales reporting. The developed system improves the effectiveness of data management, accelerates information retrieval, facilitates sales monitoring, and produces more accurate and integrated sales reports. Keywords: Information System, Sales Tracking, Laravel, MySQL, Web.